An extraordinary tribe of Tropiduchidae from the Eocene Baltic amber (Hemiptera: Fulgoromorpha: Fulgoroidea) - Szwedo, Jacek; Stroiński, Adam (Zootaxa, 2013)
The new tribe Patollini trib. n. of the Tropiduchidae with the extinct genus Patollo gen. n., comprising two species Patollo natangorum sp. n. and P. aestiorum sp. n. from Eocene Baltic amber is described. Taxonomic placement of some fossil taxa ascribed to Tropiduchidae is discussed. The classification of Tropiduchidae is discussed, as well as phylogenetic position and fossil record of Tropiduchidae and related taxa.